Biodiesel Production from POME (Palm Oil Mill Effluent) and Effects on Diesel Engine Perfor-mance - Suardi; Purwanto, Moch; Kyaw, Aung Ye; Setiawan, Wira; Pawara, Muhammad Uswah; Alfawan (International Journal of Marine Engineering Innovation and Research, 2025)
One way to reduce the scarcity of fuel oil is to make environmentally friendly alternative fuels such as biodiesel. The utilization of biodiesel can be a new energy source and also help reduce the excessive use of fuel, especially diesel and diesel oil in Indonesia. In Indonesia, the amount of palm oil will reach 49.7 tons by 2021, and this data is up 2.9% from the pre-vious year. Palm fruit is processed into CPO. More palm oil processing will produce waste called POME (Palm Oil Mill Effluent). The diesel engine transesterification method is suitable for the manufacture of biodiesel. The amount of base on the catalyst's surface affects the catalyst's activity. So that the higher the base value on the catalyst, the higher the yield of biodiesel that will be produced. The biodiesel produced will be tested on a 4-stroke diesel engine with a B5 and B10 blending composition. The study's results showed that the density and viscosity values for B5 were 5.8 cSt and 810 Kg/m3 and for B10 were 6.3 cSt and 860 Kg/m3. As for engine performance, power, torque, and SFC for B5 fuel at 4000-watt load conditions and 1000 Rpm, engine speeds are 1.18 Kw, 11.28 Nm, and 256.8 gr/Kw. B10 at 4000-watt load condition and 1000 Rpm engine speed is 1.16 Kw, 11.12 Nm, and 269.2 gr/Kw.